1989
DOI: 10.1097/00000658-198901000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic TNF Infusion Causes Anorexia But Not Accelerated Nitrogen Loss

Abstract: It has been proposed that many of the physiologic and metabolic changes that occur during critical illness and malignancy are mediated by the cytokine tumor necrosis factor alpha/cachectin (TNF). To test this hypothesis, a study of the metabolic responses that occurred during 5 days of continuous intravenous (I.V.) infusion of TNF both in rats and tumor-bearing humans was conducted. TNF administration was associated with anorexia, fluid retention, acute phase responses, and negative nitrogen balance. In both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(28 citation statements)
references
References 14 publications
1
25
0
2
Order By: Relevance
“…Similar studies of TNFa or IL-1b, however, have not been reported in infants, either in humans or in animal models. Nonetheless, increases in cytokines and reductions in energy intakes observed in these investigations are consistent with the limited available animal and human studies and other reports associating proinflammatory cytokines to anorectic response to infections (McCarthy et al, 1985;Socher et al, 1988;Michie et al, 1989).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar studies of TNFa or IL-1b, however, have not been reported in infants, either in humans or in animal models. Nonetheless, increases in cytokines and reductions in energy intakes observed in these investigations are consistent with the limited available animal and human studies and other reports associating proinflammatory cytokines to anorectic response to infections (McCarthy et al, 1985;Socher et al, 1988;Michie et al, 1989).…”
Section: Discussionsupporting
confidence: 91%
“…These and related observations in human and animal studies (McCarthy et al, 1985;Socher et al, 1988;Michie et al, 1989) also suggest that DHA and EPA supplementation may attenuate anorectic responses to infectious illness.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…First, both leptin and TNFa are produced by adipose tissue proportionally to the amount of fat stores 11Y12Y27À29 and are capable of affecting feeding behaviour and energy Leptin and TNFa system in the obese F Corica et al expenditure. 6,30,31 Second, leptin and TNFa production seem to be enhanced through the same pathways 18,32 and their mRNA expression increases during weight gain and falls during weight loss. 12,28 Third and ®nally, lower plasma leptin levels have been found in TNFa-de®cient mice with respect to wild-type animals, 19 and TNFa administration has been shown to be able to increase circulating leptin concentrations in patients with solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Whether TNF-␣ alone is sufficient to cause muscle atrophy in vivo, however, is controversial. Accelerated muscle protein degradation or decreased protein content has been reported after TNF-␣ administration in some studies but not in others (10,15,16,29,33,36).…”
mentioning
confidence: 95%